2015
DOI: 10.1016/j.ijpsycho.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Infant cortical electrophysiology and perception of vowel contrasts

Abstract: Cortical auditory evoked potentials (CAEPs) were obtained for vowel tokens presented in an oddball stimulus paradigm. Perceptual measures of vowel discrimination were obtained using a visually-reinforced head-turn paradigm. The hypothesis was that CAEP latencies and amplitudes would differ as a function of vowel type and be correlated with perceptual performance. Twenty normally hearing infants aged 4–12 months were evaluated. CAEP component amplitudes and latencies were measured in response to the standard, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 60 publications
2
22
1
Order By: Relevance
“…Recent research has shown that measurements of objective auditory evoked potentials could reveal speech discrimination abilities in infants and young children (Cheour-Luhtanen et al, 1995; Cone, 2015; Small et al, 2017). Other research groups have demonstrated the use of behavioural measures of discrimination by using a visual reinforcement paradigm (Uhler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that measurements of objective auditory evoked potentials could reveal speech discrimination abilities in infants and young children (Cheour-Luhtanen et al, 1995; Cone, 2015; Small et al, 2017). Other research groups have demonstrated the use of behavioural measures of discrimination by using a visual reinforcement paradigm (Uhler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the results were satisfactory during the first month of life, light sleep (or REM sleep) time decreases with increasing age (25) , which could compromise the results from the cortical auditory assessment in older children. Several studies have been conducted in children from three months; however, the CAEP results were obtained with the children in an alert state (13,(19)(20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral state of children during the electrophysiological assessments is an important factor for detection of auditory responses. For short-latency auditory evoked potentials it is necessary for the individual to be in a state of sleep (21) , while there is influence of the behavioral state for cortical and middle auditory evoked potentials, since assessments depend on skills such as attention and auditory discrimination (2,20) .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the P1-N1-P2 complex suggests that the speech was coded at the level of the auditory cortex and the absence of response is consistent with some imprecision in this process (6,13,14,15) . Some authors have carried out studies on the influence of vowel and consonant speech stimuli on long-latency auditory evoked potentials in children and adults with normal hearing, and could observe that there was influence on the measurements of the components P1, N1, N2 and P3, due to the level of complexity of the speech stimulus (16,17) . Therefore, the hypothesis of this study was to understand how such stimuli influence the generation of auditory evoked potentials and their components.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, because the maturational process is not complete, variations in the response in relation to the acoustic complexity of the speech stimulus and difficulty in its processing are expected (13,14,15,16) . Authors emphasized that using these potentials is important when elicited by speech stimuli, since they allow the monitoring of auditory development in normal children and in children at risk of developing communication disorders and language impairments (17) . This issue needs further investigation, but it is current and extremely important and may result in the determination of normality standards, in addition to help in the interpretation of these measures in different clinical populations.…”
Section: Introductionmentioning
confidence: 99%